Assessment of C Fibers Evoked Potentials in Healthy Subjects by Nd : YAP Laser - Elena Ammendola; Giusy Tancredi; Katia Ricci; Giovanni Falcicchio; Massimiliano Valeriani; Marina de Tommaso (Pain Research and Management)
Introduction. Although laser stimuli activate both Ad- and C-fibres, the corresponding laser evoked potentials (LEPs) remain restricted to the Ad-fibers input, while the C-fibers related potential is hardly detectable. Aims. To evaluate multichannel ultralate LEPs (U-LEPs) by using Nd : Yap laser pulses in healthy volunteers to stimulation of face and lower and upper limbs, in order to estimate the reliability of C-LEPs elicited from both trigeminal and somatic sites. Methods. Twenty healthy volunteers participated in two stimulation sessions to record Aδ-LEPs and C-LEPs. We used a Nd : YAP Laser and 62 EEG recording electrodes. Stimuli parameters were set to activate either small myelinated (Aδ), eliciting purely warmth sensations, or unmyelinated (C) afferents, and eliciting pinprick sensations. Results. At the trigeminal level, we obtained a negative-positive complex in a time interval compatible with the C fibers activation. In the somatic districts, the averaged responses consisted of an earlier negative-positive complex, followed by a later one. Single trials analysis of U-LEPs showed a maximal positive peak in a time interval in the range of C fibers. Topographical analysis of U-LEPs resembled that of LEPs. All subjects exhibited readable U-LEPs in at least 2 stimulated sites. Discussion. A purely warmth sensation seems to correspond to Aδ and C-fibers coactivation, at least in the somatic districts. While the related cortical waves seem hardly readable, their total absence could be a sign of systemic involvement of warm related C-fibers in specific clinical conditions.